Cloud – IAAS security threats and its possible mitigations - Priyadarshini, R; Malarvizhi, N (International Journal of Engineering and Technology, 2018)
Cloud IaaS, a virtual data center is an instant computing infrastructure provided and managed over the Internet. The provider owns the resource and maintains it in the level specified in the SLA. The user is permitted to use the resources as services like operating systems, security, networking, application developing servers, application deploying tools, databases, etc., on the basis of pay-per-use model. The providers and users both are concerned over integrity, privacy and security issues. This study distinguishes the issues identified with the cloud IaaS layer and strategies to overcome them to maximize the performance.